Marine Fisheries of Andhra Pradesh: A Decadal Analysis - Maheswarudu, Gidda; Rao, G Syda; Rohit, Prathibha; Laxmilatha, P; Ghosh, Shubhadeep; M, Muktha (Indian Journal of Fisheries, 2013)
The catch and effort data of marine fisheries of Andhra Pradesh was analyzed for 11 years from 2000 to 2010. The annual average marine fish landing of Andhra Pradesh during 2000 – 2010 was 1.99 lakh t. The total fishing effort in terms of fishing units declined by 33% and in terms of fishing hours declined by 9% over the time period. Pelagic finfishes were the dominant group contributing 55.6% to the total marine catch, followed by demersal finfishes (27%), crustacean resources (14.4%) and the molluscan resources (1.1%). Trawls were the major gears contributing 44.24% to the total catch, followed by gillnets (23.95%). There have been minor changes in the species composition of pelagic resources over the decade. Similar scenarios were observed in the crustacean landings, wherein the landing of penaeid prawns has increased over the years by 21% from 22657 t in 2000 to 27408 t in 2010, as against that of non penaeid prawn landings which have decreased by 12.3% from 2685 t in 2000 to 2354 t in 2010. The catch trend of major fish species was analyzed. The catch of oil sardine and mackerel showed wide inter-annual fluctuations. Oil sardines fluctuated from a maximum of 19125 t in 2000 to a minimum of 1068 t in 2002. Mackerel landings fluctuated from a maximum of 22763 t in 2009 to a minimum of 6418 t in 2007. Other pelagic resources namely carangids and tunas have registered continuous increase in catch over the years; the former from 9964 t in 2000 to 13268 t in 2010 and the latter from 2899 t in 2000 to 10515 t in 2010. Around one third of the tunas landed were contributed by the yellowfin tuna, Thunnus albacares caught mainly in hooks and lines. Their landing has increased on an average at Visakhapatnam from a meager 395 t during 2001-2005 to 2918 t during 2006-2010. The perception of tuna fishing changed with the advent of oil drilling at Kakinada and Visakhapatnam in which congregation of yellowfin tunas on the surface waters were observed which were found associated with their favoured prey, squid attracted to the surface by huge lights used by the drilling people. Landings of some of the demersal resources namely, threadfin breams, croakers, lizardfishes and goatfishes have also increased substantially during the period. Threadfin bream landings have increased by 348.9% from 1209 t in 2000 to 5427 t in 2010, croaker landings by 50.8% from 8054 t in 2000 to 12142 t in 2010, lizard fish by 297.7% from 1062 t in 2000 to 4224 t in 2010 and goat fish by 129.3% from 3501 t in 2000 to 8027 t in 2010. Among crustacean resources crabs have shown the highest increase in landings by 125.4% from 2791 t in 2000 to 6292 t in 2010. Cephalopod resources have also shown a substantial increase of 282% during the period ranging from 1011 t in 2000 to 3862 t in 2010. The assessment of trawl fishery at Visakhapatnam from 2007 to 2010 with reference to yield/recruit at SSB0.2 reported that eleven out of the fifteen commercially important resources are currently over exploited. They are Trichiurus lepturus, Pennahia macrophthalmus, Saurida undosquamis, Metapenaeus monoceros males and females, Metapenaeus dobsoni males and females, Portunus sanguinolentus males and females, Sepia aculeata and Loligo duvaucelli.